EVALUATION OF THE EFFECTIVENESS OF THE NON-KILNED ASH-SLAG GRAVEL STRUCTURE UNDER THERMAL IMPACT - Atyaksheva, A.V.; Seitova, Zh.A.; Issataeva, A.K.; Ryasnov, D.Yu.; Khamitova, Ye.M. (Eurasian Physical Technical Journal, 2026)
The article presents an analysis of the stress-deformed state results for gravels based on ash-slag mixtures, with the same specified composition, but different in structure and density under the thermal impact with temperature 500 °C. The evaluation of the gravels structure was carried out in a numerical simulation of the thermostatic structural analysis process. According to the results, the two – component gravel structure shows greater thermal stability. Separation into two component structure leads to a more even distribution of iso Surfaces, which in turn eliminates the possibility of stress surges leading to sharp changes in the structural characteristics of materials accompanied by degradation processes. In two component structure, there is a reduction of a stress intensity resulting from sudden stresses surges and leading to the formation of material failure points. The maximum stress intensity of two component gravel for about1.8 ‧106 Pa in compare of single component for about 2.1‧107 Pa. The higher thermal viability of two-component gravel is demonstrated by thermal deformation due to a reduction in shear stress, which is (max) 9.03‧105 Pa, in compare of single component (max) 1.11‧107 Pa. Such conditions of the stress-deformed state indicate a greater reserve of thermal resistance for two – component gravel in compare of single component gravel and the possibility of its use as a heat protection in the composition of heat-resistant panels or independently in the temperature range up to 500°C.